Tutorial pembuatan media pembelajaran berbasis kuis oodlu - Sari, Arik Mustika (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The aim of this research can be used to determine the extent of the development of the Oodlu quiz media on grade 4 elementary school students' eye sense material and to determine the feasibility of Oodlu learning media on grade 4 elementary school students' five sense material. Research on the development of this quiz media has gone through a validation process. Based on validation that has been tested by experts, the research developed has results that are suitable for use during learning and have been declared valid by experts. This research is about the development of oodlu quiz learning media. Researchers use quiz-based learning media to refresh the classroom atmosphere which was previously boring to make it more enjoyable. In developing this oodlu quiz media, researchers used the 4D development stages or processes, namely Define, Design, Develop and Disseminate. Based on the research results, this research is quite effective when used during elementary school learning. It can be concluded that Oodlu quiz-based learning media can increase students' motivation and activeness in learning media that is more practical and fun and makes it easier for students in terms of learning interactions.